Deviation of the acoustic pressure to particle velocity ratio from the ϱc value in liquids and solids at high pressuress - FILIPCZYŃSKI, Leszek; GRABOWSKA, Anna (Archives of Acoustics, 1989)
Basing on fundamental equations of nonlinear acoustics the authors determined the ratio of the acoustic pressure to the particle velocity p_a/u for a travelling plane wave as a function of condensation. Nonlinear effects in the medium depend on the nonlinearity parameter B/A and on the maximum pressure. As the measure of those nonlinearities, the deviation of the p_a/u ratio from the ϱ_0c_o value was introduced and computed for water, fat tissue, steel and aluminium alloy, up to pressures of 100 MPa. The B/A value for steel and aluminium could be determined basing on acousto-elastic properties of these metals. In this way it could be shown that the capacitance hydrophone, used for measurements in lithotripsy, does not introduce nonlinearities caused by its steel front plate when measuring nonlinear acoustic pressure fields. For, the mentioned deviation is two orders of magnitude lower for steel than for water and soft tissues.